Financing Businesses in Africa : The Role of Microfinance - Aggarwal, Shilpa; Klapper, Leora; Singer, Dorothe (2012)
This paper evaluates how microfinance performed in providing business financing in 27 Sub-Saharan African countries. It uses data from the 2009 and 2010 Gallup World Poll, a nationally-representative survey of at least 1,000 individuals per country, conducted in up to 157 countries per year. The data, supported by rigorous statistical evidence in related literature on the use of microcredit around the world, demonstrate that economic gains from microcredit have been more modest than what was once believed. On the other hand, the analysis suggests that the poor save in order to start new businesses and that the introduction of formal products for small savings can be a key financial innovation. The authors also analyze the challenges the poor face in setting money aside to save, and discuss what policymakers can do to promote savings.